Pervasive alteration of tree communities in undisturbed Amazonian forests - Nuture - Val, Adalberto Luis; Silva, M. N.P.; Val, Vera Maria Fonseca Almeida e (African Zoology, 1998)
In addition to seasonal long-term changes in dissolved oxygen and carbon dioxide, water bodies of the Amazon present periodic short-term episodes of hypoxia and even anoxia. To preserve gas exchange and acid base balance fish of the Amazon have developed multiple adaptive solutions which occur at all biological levels.These solutions are thought to represent adaptive convergence rather than phylogenetic relatedness. Fish of the Amazon exposed to different experimental conditions adjust, for example, several parameters to improve oxygen transfer from the gas-exchange site to the tissues. These parameters include morphological changes such as the development of the lower lip in Colossoma, changes in ventilation rates, changes in circulatory parameters, increased circulating red blood cells, decreased levels of intraerythrocytic phosphates, and adjustments of intraerythrocytic pH (pHi). These adjustments that allow fish to survive both short- and long-term hypoxia occur in different degrees in different fish species and may or may not occur simultaneously. In addition, these adjustments in oxygen transfer affect many other parameters, particularly acid-base status. We suggest that these adjustments are initiated as soon as the animal detects the environmental change in oxygen availability and are mediated by a single factor, possibly one of the catecholamines. In this paper we aim to show that adaptation to hypoxia is a never-ending task for the fish of the Amazon.